Analisis Pengelolaan dan Pemanfaatan Dana Non-Halal pada Bank Syariah Indonesia Cabang Bengkalis - Rozi, Fachrul; Tomisa, Muhammad Elsa; Suhartini, Ade; Oktayani, Dewi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Analysis of The Management and Utilization of Non-Halal Funds at BSI KCP Bengkalis for 2022-2023. The purpose of this study is to find out how the practice of managing and utilizing Non-Halal Funds, especially in BSI KCP Bengkalis, as well as determining how the income and sources of non-halal funds. As well as writing non-halal fund reports on the BSI side and allocating these funds whether they are in accordance with the Fatwa DSN–MUI as a social fund intended for social activities. This research method uses qualitative research that produces data that cannot be achieved by using qualitative research that produces data that cannot be achieved using statistical procedures. This research uses skunder data sourced from the financial statements of the BSI KCP Bengkalis Company, namely the report on the source and use of benevolent funds. The method of data analysis in this study is data reduction, namely summarizing, choosing the main things, presenting data, and verifying / concluding. The collection of research data was in the form of interviews by conducting questions and answers directly to respondents, namely accounting staff at BSI KCP Bengkalis. The results of the interview were analyzed by comparing the Fatwa DSN-MUI that applies to the management and utilization practices applied. The conclusion of this study is that the use of non-halal funds is really applied in Islamic banking.